HIPPIES’ SOCIAL THREATS AND SOLUTIONS POTRAYED IN THE FILM BAD TIMES AT EL ROYALE - Sofian, Ela Sofiarti; Putu Setiarini, Ni Luh (Journal of Language and Literature, 2020)
As an art, literature and film offer ways of seeing and feeling new things without having to experience them ourselves. They can also function in society as a means of both criticizing and affirming cultural values, as well as describing historical events throughout the years. Thus, this study aims to explore representations of social threats posed by the hippies toward American society in the late 1960s as depicted in the film ‘Bad Times at the El Royale’. Besides, this study also aims to investigate the solutions performed by the rest of the American population in overcoming the threats as demonstrated in the film. The data of this study are the utterances and scenes reflecting the social threats and solutions portrayed in this film. The method of this study was qualitative methods. Results show that the social threats posed by the hippies are determined through the contrast between the American values and the hippie values as depicted in the film, while the solutions are interpreted based on what actually happened according to history.